PENGEMBANGAN SISTEM INFORMASI DAN APLIKASI PELAYANAN DI UPT BALAI BAHASA UNP BERBASIS ANDROID - Edi Prasetio; Yeka Hendriyani (Universitas Negeri Padang, 2019)
The UPT Balai Bahasa Universitas Padang is one of the language institutions that opens services for the entire academic community and the general public, because along with the increasing need for English language skills. The services available include Language Test, Language Course, and Document Translation. The number of services available, but still using manual methods. So that it can cause data loss, as well as errors in calculating values. To overcome these problems, a system is needed that can assist in the service process at the UNP Language Unit. This system design is implemented using the PHP programming language, with the MYSQL database. In system design, it is involved Use Case Diagram, Activity Diagram, Context Diagram, Flowmap, Normalization, and Entity Relationship Diagram. This system involves at least 4 users, namely Administrator, Head of UPT, Instructor / Officer, and Customer. All registered users have access rights to the system by logging in using email and passwords with MD5 encryption. The information system built produces a client server based application, where the website as a server application and android platform as a client application. Keywords: Information System, Service aplications, PHP, database MYSQL.